Maintaining and sustaining task performance using strategic thinking in process orientation - Fauzi, Wan Jumani; Najah, Osman; Wan Azlee, Wan Abdullah; Ghani, Airin Abdul; Abdullah, Aziman; Abdullah, Ibrahim (2011)
This study provides empirical evidence that indicates that there is a positive relationship between higher attempts of strategic thinking skills activities with successful task performance. The results also indicated that there is significant difference in the learners' motivation after going through process oriented learning through the use of Strategic Thinking Skills Taxonomy online. Implications of the study are discussed along with suggestions for future research.